1995
DOI: 10.1111/j.1949-8594.1995.tb10191.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Preservice Elementary Teachers' Sense of Efficacy in Teaching Science

Abstract: This paper reports progress to date on a longitudinal study of changes in preservice teachers' sense of efficacy in teaching science. The study involved procedures designed to validate, in an Australian context, the Science Teaching Efficacy Beliefs Instrument (STEBI‐B) comprised of two scales: Personal Science Teaching Efficacy Belief Scale (STE) and Science Teaching Outcome Expectancy Scale (STO). Concomitantly, the instrument was used to monitor changes in teachers' sense of science teaching efficacy employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Contextual factors for teacher self-efficacy found in previous research include collective teacher efficacy (Goddard et al, 2000;Goddard et al, 2004;Skaalvik & Skaalvik, 2007), and support from parents and school administrators (Klassen & Chiu, 2010;RameyGassert, et al, 1996;Skaalvik & Skaalvik, 2007;Skaalvik & Skaalvik, 2010). Similar to previous finding on the relationship between teacher self-efficacy and collective teacher efficacy, this research shows influence from other teachers on self-efficacy of Chinese language teachers.…”
Section: Contextssupporting
confidence: 77%
See 2 more Smart Citations
“…Contextual factors for teacher self-efficacy found in previous research include collective teacher efficacy (Goddard et al, 2000;Goddard et al, 2004;Skaalvik & Skaalvik, 2007), and support from parents and school administrators (Klassen & Chiu, 2010;RameyGassert, et al, 1996;Skaalvik & Skaalvik, 2007;Skaalvik & Skaalvik, 2010). Similar to previous finding on the relationship between teacher self-efficacy and collective teacher efficacy, this research shows influence from other teachers on self-efficacy of Chinese language teachers.…”
Section: Contextssupporting
confidence: 77%
“…Teacher self-efficacy may also be domain specific. For example, according to previous research (Ginns, Watters, Tulip, & Lucas, 1995;Ramey-Gassert, Shroyer, & Staver, 1996), teacher's self-efficacy is correlated with teacher's preference in the subject and teacher's previous subject-related learning or professional development. Ramey-Gassert et al (1996), for example, revealed that science teachers who had successful experiences in learning science or overcoming challenges in science subjects demonstrate more favourable attitudes toward science, which contributes to their self-efficacy in teaching science.…”
Section: Teacher Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The development of teacher efficacy and classroom management beliefs among pre-service teachers has been investigated by the many researchers, because once these beliefs are established, they would show resistance to change (Ginns, Tulip, Watters, & Lucas, 1995;Fortman & Pontius, 2000;Lorna, Neelam, & Kyesha, 2002). Pintrich (1990) suggested that teachers' beliefs would ultimately prove to be the most valuable psychological construct to teacher education.…”
Section: Introductionmentioning
confidence: 99%
“…Preservice teachers who are expected to engage in teaching science in elementary school commonly hold low self-efficacy beliefs about their ability to teach science after graduation (Enochs & Riggs, 1990;Ginns, Watters, Tulip, & Lucas, 1995;Ginns & Watters, 1996;Watters, Ginns, Enochs & Asoko, 1995). This low sense of self-efficacy militates against them engaging effectively in learning science.…”
Section: Situation or Contextmentioning
confidence: 99%